2015
DOI: 10.5897/jdae2014.0577
|View full text |Cite
|
Sign up to set email alerts
|

Marketing and market integration of cowpea (Vigna unguiculata L. Walp) in Uganda

Abstract: Despite the importance of cowpea in Uganda as a leading legume, its production and improvement have not received much attention over the last two decades. Data was obtained on prices of grains of cowpeas on a weekly basis from FIT Uganda between 2008 to 2011 in Soroti, Lira and Kampala. Data collected was analyzed using descriptive statistics, particularly, frequencies and the measures of central tendency. Several approaches were used to investigate the degree of cowpea market integration in Uganda: bivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…This implies that the market price of cowpea in the study areas has no much significant variance according to the evidence from the results of the study. This is result is consistent with (Ddungu et al, 2015) who asserted that there is an indication of seasonal variations. As expected, cowpea grains are cheaper during the harvest period and immediately afterwards.…”
Section: Results and Discussion Socio-economic Characteristics Of The...supporting
confidence: 92%
See 1 more Smart Citation
“…This implies that the market price of cowpea in the study areas has no much significant variance according to the evidence from the results of the study. This is result is consistent with (Ddungu et al, 2015) who asserted that there is an indication of seasonal variations. As expected, cowpea grains are cheaper during the harvest period and immediately afterwards.…”
Section: Results and Discussion Socio-economic Characteristics Of The...supporting
confidence: 92%
“…Price is a determining factor for profit making in marketing when the price is favorable marketers may decide to carry their products to the market. This is in line with the findings of Ddungu et al (2015) who posited that prices of the agricultural commodities found in different markets locations are majorly influenced by the nature of its seasonality in production, fluctuations in the production output and the general economic environment within a country. This king of price variability becomes a common phenomenon in agricultural outputs due to stochastic nature of the products.…”
Section: Sources Of Transportation Of Cowpea Produce To the Market By...supporting
confidence: 90%
“…It describes the interactions between two spatially separated marketplaces in general. A well-integrated market system is necessary not only for efficient allocation of productive resources, but also for the reduction of pricing risks that threaten economic actors' well-being, particularly the poor and food insecure households [10]. This is because the strength of price signals communicated between different market levels is crucial to the effectiveness of market changes [31].…”
Section: Introductionmentioning
confidence: 99%